Voluntary environmental agreements, emission taxes and international trade: The importance of the timing of strategies - Klaus Conrad (Fondazione Eni Enrico Mattei (FEEM), 1999)
The purpose of the paper is to narrow the gap between the widespread use of voluntary agreements and research on the rationale of such approaches. A typical example are voluntary agreements of many industries to reduce carbon dioxide emissions because of global warming. If the industry anticipates that taxes and fees will be introduced in the coming years, it seems rational to act in advance in order to mitigate the tax levels. The conventional approach in strategic trade and tax models was to look at a two-stage game where governments set taxes first and then firms react. In such a policy regime the government is concerned about the international competitiveness of its firms and sets taxes below marginal damages. In this paper, we consider a policy regime with a reversed timing. Firms commit themselves in the face of emission taxes to abatement efforts and to lower levels of the environmentally intensive output. Then the government introduces the tax. Under this timing of strategies the tax is equal to marginal damage. Firms waive profit and reduce output in order to use less of the polluting input. The reward for this behaviour will be a less strict use of policy instruments and hence lower abatement costs in the near future.
Keywords: D43; F13; H23; 330; Environmental policy; Strategic trade policy; Emission taxes; Voluntary agreements; Umweltpolitik; Selbstverpflichtung; Umweltabgabe; Ökosteuer; Spieltheorie; Internationale Handelspolitik; Theorie